Lower Gastrointestinal Bleeding - Jagtap, Nitin; Reddy, D. Nageshwar; Tandan, Manu (Journal of Digestive Endoscopy, 2022)
Lower gastrointestinal (LGI) bleeding indicates bleeding from colon or anorectum. Typically, patients with LGI bleeding present with bright red blood per rectum or hematochezia, although rarely they can present with melena as well. Alternatively, LGI bleeding is also defined as bleeding from a source within potential reach of a colonoscope, that is, colon and terminal ileum. LGI bleedings have more favorable outcomes than upper GI (UGI) bleeding and less common than UGI bleeding. Any patient presenting with GI bleeding should undergo a detailed history and physical examination for clues that may suggest source and possible etiology. Colonoscopy remains the most widely used and preferred instrument of choice for both diagnosis and therapy. This review will discuss in brief the causes, triaging, and role of colonoscopy in the management of LGI bleeding.
Keywords: colonoscopy; hematochezia; hemostasis; lower gastrointestinal bleeding